2012
DOI: 10.1007/s12011-012-9526-2
|View full text |Cite
|
Sign up to set email alerts
|

C-Phycocyanin Modulates Selenite-Induced Cataractogenesis in Rats

Abstract: The present investigation is aimed to evaluate the anticataractogenic potential of C-phycocyanin (C-PC), extracted and purified from Spirulina platensis. Enucleated rat lenses were maintained in vitro in Dulbecco's modified Eagle medium (DMEM). Group I contained DMEM, Group II and Group III contained 100 μM of sodium selenite, Group III was subdivided into three viz IIIa, IIIb, IIIc supplemented with 100, 150, 200 μg of C-PC respectively. In the in vivo study, on tenth day post partum: Group I rat pups receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Age related cataract is the leading cause of blindness associated with the accumulation of oxidative stress in the eye lens. A study on the regulatory effect of C-PC on sodium selenite-induced cataract in rats revealed that C-PC can adjust the in vivo and in vitro antioxidant enzyme levels, thereby reducing oxidative stress and the incidence of sodium selenite-induced cataract [ 129 ]. Another scholar observed secondary changes in electrolyte levels, mean activities of antioxidant enzymes (i.e., SOD, CAT), and reduced glutathione during sodium selenite-mediated cataractogenesis in rats; this scholar also found that the deleterious effects of sodium selenite toxicity can be restored by simultaneous treatment with C-PC [ 130 ].…”
Section: Antioxidationmentioning
confidence: 99%
“…Age related cataract is the leading cause of blindness associated with the accumulation of oxidative stress in the eye lens. A study on the regulatory effect of C-PC on sodium selenite-induced cataract in rats revealed that C-PC can adjust the in vivo and in vitro antioxidant enzyme levels, thereby reducing oxidative stress and the incidence of sodium selenite-induced cataract [ 129 ]. Another scholar observed secondary changes in electrolyte levels, mean activities of antioxidant enzymes (i.e., SOD, CAT), and reduced glutathione during sodium selenite-mediated cataractogenesis in rats; this scholar also found that the deleterious effects of sodium selenite toxicity can be restored by simultaneous treatment with C-PC [ 130 ].…”
Section: Antioxidationmentioning
confidence: 99%
“…Spirulina is a genus of planktonic blue–green algae found in the alkaline water of volcanic lakes. Several in-vitro experiments have shown that Spirulina and its extracts, especially CPC, exhibit a variety of pharmacological effects, such as neuroprotective effects [ 12 ], hepatoprotective abilities [ 13 ], renoprotective effects [ 14 ], cardiovascular protective effects [ 15 ], and the elimination of cataracts [ 16 ], which is generally attributed to the antioxidant and free radical scavenging properties of CPC. Several studies have shown that the antioxidant activity is related to not only the bilin chromophore but also the apoprotein [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that effects of C-PC, a billiprotein pigment in the incidence of selenite-induced cataract both in vitro and in vivo [21]. It has been documented that C-PC evades oxidative stress and related cellular damages by scavenging the free radicals and chelating metal ions [41].…”
Section: Resultsmentioning
confidence: 99%
“…C-PC was extracted by standard method as described in our previous publication [21]. All the chemicals used in the experiment were of analytical grade (HIMEDIA, Mumbai, India).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation